Penyelesaian Sengketa Perjanjian Pembiayaan Layanan Kredit Digital (PayLater) Akibat Wanprestasi: Analisis Mazhab Fikih dan Hukum Positif - Sukma, Melati; Wijaya, Abdi; Sofyan, Sofyan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The purpose of this study is to determine the legal position of the digital credit service financing agreement (PayLater) according to the fiqh school, to determine the legal position of the digital credit service financing agreement (PayLater) according to positive law. To find out how to resolve disputes over digital credit service financing agreements (PayLater) due to default. In answering these problems, the author uses normative (syar'i) and juridical theology. This research is classified as library research (library research), data collected using library data in the form of books, journals, articles in both electronic media and print media as data, then analyzes the contents of the literature relating to the problems discussed, then reviews and The results of this study show that the scholars of the madhhab agree that in this transaction it is not allowed to qardh which aims to bring profit to the borrower. Meanwhile, according to positive law, the position of debt and receivables is explained in OJK Regulation Number 77/POJK.07/2016 concerning Information Technology-Based Money Loan Services which regulates the implementation of Fintech peer to peer lending (P2PL) as business actors who pay attention to the form of registration and licensing of the organizing institution, future governance and risk management and periodic reports to the OJK as well as a form of education to consumers regarding legal protection. And based on the positive law that applies in Indonesia, there are two routes that can be used in dispute resolution, namely the litigation route and the non-litigation route. In dispute resolution carried out by the lender and the loan recipient, they do not choose to use dispute resolution methods with these channels, but the lender and loan recipient prefer to carry out internal settlements, and provide administrative sanctions for defaulters.